IDENTIFICATION OF Q2933P MUTATION IN FAT1 GENE IN A PATIENT WITH INTECLLECTUAL DISABILITY FROM DIOXIN VICTIM’S VIETNAM FAMILY - Thanh Ngan, Nguyen Thi; Kim Lien, Nguyen Thi; Hien, Nguyen Thu; Lan, Nguyen Ngoc; Tung, Nguyen Van; Kim Dung, Le Thi; Hien, Nguyen Thi; Ton, Nguyen Dang; Hoang, Nguyen Huy; Hai, Nong Van (Vietnam Journal of Biotechnology, 2018)
Dioxins are a group of chemicals known as highly toxic environmental persistent organic pollutants (POPs). Numerous dioxin-like compounds have been identified, such as polychlorinated dibenzo-p-dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs), polychlorinated/polybrominated biphenyls (PCBs/PBBs), and 1,4-dioxin.  The singular term dioxin refers to the most toxic compound, 2,3,7,8-tetrachlorodibenzodioxin (2,3,7,8-TCDD). Dioxin pollution caused by chemical warfare has been causing serious consequences to the ecological environment and especially to the health of Vietnamese people. In particular, dioxin was demonstrated to be the cause of many diseases, including diseases related to the nervous system of which intellectual disability is one of the 17 diseases have been recognized by Vietnam. Deformities, birth defects, intellectual disability have been detected in F1 and F2 generations of the exposed victims. Dioxin may cause changes in the whole genome / genome expression (exome), or the structure and function of the gene that leads to pathogenesis in the exposed people and the genetic changes can be passed on to the next generations. In the present study, the Whole Exome Sequencing (WES) method was used to analyze and identify genetic variants related to the intellectual disability in a dioxin exposed victim’s family in Vietnam. The screening results revealed that a Gln2933Pro heterozygous mutant in the FAT1 (Fat atypical cadherin 1) gene of the patient was inherited from the patient’s father whose high blood concentration of dioxin, as well as illustrated the changes in the protein structure. In addition to the important scientific implications, this result might be essential for providing counseling for families who are the dioxin victims.